Magazine “Slavs” in Structure of Foreign Policy “Soft Power” in Slavic Movement during the Great Patriotic War of 1941-1945: Musical and Cultural Aspect - O. V. Tuzova (Научный диалог)
For the first time, an attempt has been made to source-based analysis of materials on musical subjects of the “Slavs” magazine, the press organ of the transnational anti-fascist All-Slavic Committee in the conditions of the Great Patriotic War of 1941-1945. The relevance of Slavic musical problems in the socio-political and research terms is shown. Officially approved personalities of outstanding musicians, including opinion leaders - contemporaries of the war, whose names are found on the pages of the magazine, are revealed. It has been established that the attribution of most information units on musical art issues published in the magazine is difficult. Socially significant musical events in the country and abroad highlighted in the magazine, having local and international resonance: the premiere of the Seventh Symphony of D. D. Shostakovich, performances, concerts, accompaniment of various political and scientific events, etc. are singled out. The diverse use of the Slavic cultural potential in the musical sphere is shown. The main national informational musical and cultural vectors reflected in the publications (Russian, Ukrainian, Belarusian, Czech, Polish) are determined. The key contexts of the magazine’s publications are noted - the struggle against the common enemy - fascist Germany, the liberation and restoration of the culture of the Slavic countries.